Pengaruh Harga, Kualitas Produk, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada E-Commerce Shopee (Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Chicha Fahriana; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to analyze and describe the effect of price, product quality, and service quality on purchasing decisions on e-commerce shopee (study of 2018 class of economic and business faculty students). The population in this study were undergraduate students of the Faculty of Economics and Business, Islamic University of Malang Batch 2018 both from the Management study program as many as 518 students, Accounting as many as 275 students, and Sharia Banking as many as 106 with a total of 899 people. Then 90 people were taken from this number using the slovin formula. The variables used in this research are purchasing decision variables (dependent variable), while the independent variables are price, product quality, and service quality.The results of this study conclude that there is a positive and significant influence between price, product quality, and service quality variables on purchasing decisions and simultaneously concludes that there is an influence between price, product quality, and service quality variables on purchasing decisions. Keywords: Purchase Decision, Price, Product Quality, Service Quality